Πρώτες ειδήσεις για τον ναό Αγίου Νικολάου Λόχμης Γρεβενών και τις τοιχογραφίες του - Τσιλιπάκου Αγαθονίκη Δ. (Μακεδονικά, 2011)
The church of St. Nicholas stands in the cemetery at the community ofLochmi (previous name Vitsi) in the Municipality of Grevena. It is a singlenave church, dated to the beginning of the 18th century, with semi-circularapse of the sanctuary and an extensive narthex. It is a typical pattern of thearchitecture of churches in the region Grevena in the 17th to the 18th century, with morphological features that are indigenous in churches and catholikaof monasteries, mainly in Epirus, Thessaly and Macedonia.The church is decorated with wall paintings, which we ascribe to different artists (A and B). The painter A storied, about 1717, the sanctuary andthe east wall of the narthex. In the same period he made also the paintings ofthe sanctuary in the church of Panagia the Source of Life at Great Sirini andcertain icons for the cancel screen of the church of St. Nicholas at Anthiro.The work of the painter A could be enlisted, because of the iconography, tothe eclecticism of the Post Byzantine period that dominated from the 17thcentury. He adopted solitary motifs and common shapes, which had beenpopular in the two «great schools» of the 16th century. He generally insistedon the synthetic local Macedonian tradition of the Palaeologan period. Histechnique belongs to the anticlassical trend of the Post Byzantine painting, farremoved from the achievements of the two «great schools» and continued theold local tradition of Macedonia and the northern parts of the Balkans. The painter B storied, about 1742, possibly after a reconstruction, themain nave of the church. His work seems to be more attached to the older LateByzantine iconographical tradition of Serbia and Macedonia, as also to the local one of the northwestern Greece from the 15th century, with special characteristics the plain and thinly populated compositions. His style tried unsuccessfully to imitate the literary trend of the return to the old Palaeologan prototypes in Mt. Athos, which has been started in the first decades of the 18thcentury with its prime exponent and representative the Athonite monk Dionysios from Fourna in Agrafa. This fact can also be appropriated to otherpainters of the same period that came from Epirus and western Macedonia.The church of St. Nicholas at Lochmi is one of the solitary monuments ofthe 18th century at Grevena, and also a most important one, that is precisely11dated. The churches of St. Nicholas and of Panagia the Source of Life atGreat Sirini could be arranged to the oldest churches that still remain in theMunicipality of Grevena. The study of the architecture and the decoration ofthe church at Lochmi, after its conservation, that becomes urgent, is going toenrich our knowledge about a relatively disregarded period of Post Byzantineart and especially in the region of western Macedonia, and will outline theroute of the travelling workshops and artists from the region of northwesternGreece and Epirus.